Beta: The good, the bad and the smart : Explaining the cross-section of Nordic stock market return variation using a two-beta model - Ihanainen, Miko (My University, 2019)
The Capital Asset Pricing Model (CAPM) is still widely used to price different assets, but it leaves a lot of questions unanswered. Several studies have come to the conclusion, that the CAPM is inadequate in pricing assets. More asset pricing models have been developed and suggested to better explain the cross-sections of stock returns, and some of them have shown a better performance than the CAPM. Previous literature has also studied the reasons that drive the time-variation in stock returns and what drives the aggregate stock market returns. A traditional economic view is that the present value of an asset is affected by the change of future cash flows or the change of discount rates that are used to discount the future cash flows. Thus, also the aggregate stock market returns can be thought to be affected from the changes in these two variables. The purpose of this study is to divide the stock’s market beta into two components. One that reflects the changes in market’s future discount rates, and one that reflects the changes in market’s future cash flows. An intertemporal investor should price these two risks separately, since they affect the future consumption possibilities differently. Negative shocks to future cash flows are riskier, since they decrease the present wealth, but do not change the future investment opportunities. Negative shocks to discount rates, do decrease the present wealth as well, but it increases the future investment opportunities. Thus, assets that covaries with the changes of market’s future cash flows should be riskier and assets that covaries with changes in discount rates should show less riskiness. Based on their riskiness, cash flow betas and discount rate betas are called bad and good respectively. The data of this study consists of Nordic stock market data from Finland, Sweden, Norway and Denmark. The study period is between 1991–2018 and betas are derived for value, size, momentum and volatility portfolios. The model to derive the two betas relies largely on earlier papers and the study is conducted for the first time with a Nordic data. Results indicate that the variables used in the model shows similarities in their explanatory power but are weaker for the Nordic countries than they were for the U.S. market. The results indicate some findings where higher average returns are associated with higher sensitivities to cash flow news. This is not the case for every portfolio and for every country, as for example in Finland, the model does not capture any differences in the riskiness of the portfolios. The results show also differences in the overall sensitivities to the news in the countries. By looking at the overall risk prices, the two-beta model does not outperform the original CAPM with the used variables.
Keywords: CAPM, ICAPM, Smart beta, beta, VAR